GAMBARAN KELUARGA BERENCANA - Maria Awaldina Dua Barbara S.S.T. M.Kes (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2022)
MKJP is a contraceptive that is used for the long term. Based on a preliminary study at PMB Neng Titing, Amd.Keb, 5 respondents were asked and answered, it was found that 2 respondents were supported by their husbands while 3 respondents were not supported by their husbands to use long-term contraception because husbands were afraid to have sex with their wives. The purpose of this study was to find out the description of husband's support regarding the use of MKJP in couples of childbearing age based on information, emotional, appreciation, instrumental at PMB Midwife Neng Titing, Amd.Keb, West Bandung Regency in 2021. Methods This research uses descriptive research. Sampling using a total sampling technique, amounting to 85 people. Data were obtained using a questionnaire and analyzed using Univariate Analysis. The results showed that more than half of the respondents did not get support from their husbands as many as 55 people (64.7%) and more than half of the respondents did not get information support from their husbands as many as 53 people (62.4%). While emotional support from husbands as many as 54 people (63.5%). It is known that more than half of the respondents did not receive support from their husbands as many as 52 people (61.2%). And 45 people did not get instrumental support from their husbands (52.9%). The conclusion of this study is that husbands do not support their wives in choosing long-term contraception. It is recommended to provide counseling and midwives can increase counseling to couples of childbearing age for husbands.